2023
DOI: 10.1159/000535085
|View full text |Cite
|
Sign up to set email alerts
|

Continuous versus Routine Electroencephalography in the Intensive Care Unit: A Review of Current Evidence

Helene Fenter,
Andrea O. Rossetti,
Isabelle Beuchat

Abstract: Background Electroencephalography has long been used to detect seizures in patients with disorders of consciousness. In recent years, there has been a drastically increased adoption of continuous EEG (cEEG) in the ICUs. Summary Despite the development of increasingly performant imaging techniques and several validated biomarkers, EEG remains central to clinicians in the intensive care unit, and is experiencing expanding indications. Not only does EEG allow seizure or status epilepticus detection, which in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…This relatively low incidence is possibly due to the exclusion of patients with neurological crises or subtle status epilepticus and a limitation of seizure detection by rEEG. cEEG has been reported to be more effective at detecting epilepsy, particularly NCSE, than rEEG is [ 8 , 23 ]. Kamel et al used cEEG to monitor patients in medical and surgical ICUs (excluding patients with acute brain injury, consistent with the exclusion criteria of the present study) and identified ESz in 11% of the patients [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This relatively low incidence is possibly due to the exclusion of patients with neurological crises or subtle status epilepticus and a limitation of seizure detection by rEEG. cEEG has been reported to be more effective at detecting epilepsy, particularly NCSE, than rEEG is [ 8 , 23 ]. Kamel et al used cEEG to monitor patients in medical and surgical ICUs (excluding patients with acute brain injury, consistent with the exclusion criteria of the present study) and identified ESz in 11% of the patients [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…cEEG studies are also useful for the prognostic evaluation of comatose patients in ICUs [ 4 , 5 ]. cEEG is more effective at detecting NCSs and NCSE than rEEG is; however, cEEG is not associated with improved outcomes compared with those of repeated rEEG [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%